2016
DOI: 10.1002/mop.30085
|View full text |Cite
|
Sign up to set email alerts
|

A wideband circularly polarized dielectric resonator antenna excited with conformal‐strip and inverted L‐shaped microstrip‐feed‐line for WLAN/WI‐MAX applications

Abstract: A new wideband circularly polarized dielectric resonator antenna (DRA) has been developed and presented in this article. The proposed antenna consisting rectangular and cubical‐shaped dielectric resonator (DR) with optimum gap excited by using combination of conformal‐strip and inverted L‐shaped microstrip‐feed‐line. The combinations of two different feeds (i.e., conformal‐strip and microstrip‐fed‐line) excite orthogonal modes in two DRs to generate circular polarization. The gap between these DRs and conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Various techniques [7–10] for ensuring circular polarization in DRAs lead to an interesting revelation. Placement of a rectangular dielectric resonator (DR) with 45° angle with respect to aperture leads to circular polarization in [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques [7–10] for ensuring circular polarization in DRAs lead to an interesting revelation. Placement of a rectangular dielectric resonator (DR) with 45° angle with respect to aperture leads to circular polarization in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ai-Lawati and Khamas [9] have made a detailed analysis to generate below 3 dB axial ratio (AR) in an elliptical DRA with conformal strip excitation. Similar conformal strip with L-shaped feed-line has also been investigated for circular polarization [10]. However, it seems that the cross-shaped slot technique is one of the economic and simple approaches for obtaining circular polarization using a single feed.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation on substrate integrated wave guide in cylindrical DRA has been reported for 4.62% impedance bandwidth . Similarly, several techniques have been adopted for obtaining circular polarization like; using single aperture technique in rectangular DRA, conformal strip in elliptical and rectangular DRA, parasitic strip with hemispherical DRA, quadrature coupler in a hollow rectangular DRA, helical conductor in cylindrical DRA, rotated notched rectangular DRA 17 have been used by some of the researchers for obtaining circular polarization in dielectric resonator antenna. Thus, many articles have shown different techniques for obtaining broadband and circular polarization, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, Al and Long have demonstrated that a dielectric resonator can play the role of an antenna . Since, in the telecommunication systems, the use of the dielectric resonator antennas (DRA) has become very common and received much attention . Indeed, the DRA has many advantages such as being more compact, stable in the temperature, have a high quality factor, low losses due to the absence of metallization in the radiating structure, easy to fabricate and to couple .…”
Section: Introductionmentioning
confidence: 99%
“…3 Since, in the telecommunication systems, the use of the dielectric resonator antennas (DRA) has become very common and received much attention. 4 Indeed, the DRA has many advantages such as being more compact, 5 stable in the temperature, 5,6 have a high quality factor, low losses due to the absence of metallization in the radiating structure, easy to fabricate and to couple. 7,8 Through the development of new dielectric materials with very low losses and very good electrical and thermal characteristics, we find that the use of dielectric resonators in microwave systems gave a remarkable development.…”
Section: Introductionmentioning
confidence: 99%